2014
DOI: 10.1371/journal.pone.0104411
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Quasi-Randomized Controlled Study of Herbal Medicine Hochuekkito as an Adjunct to Conventional Treatment for Progressed Pulmonary Mycobacterium avium Complex Disease

Abstract: IntroductionHochuekkito, a traditional herbal medicine, is occasionally prescribed in Japan to treat patients with a poor general condition. We aimed to examine whether this medicine was beneficial and tolerable for patients with progressed pulmonary Mycobacterium avium complex (MAC) disease.MethodsThis pilot open-label quasi-randomized controlled trial enrolled 18 patients with progressed pulmonary MAC disease who had initiated antimycobacterial treatment over one year ago but were persistently culture-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Hochuekkito (Bu Zhong Yi Qi Tang) (10 herbs including Daucus carota , Astragalus membranaceus , Atractylodes lancea , Bupleurum falcatum , and Angelica acutilob ), is occasionally used in Japan for the control of a weak constitution, physical weariness, anorexia, and gastrointestinal hypomotility. A recent randomized controlled trial enrolling 18 patients with an advanced stages of MAC disease revealed the significant therapeutic efficacy of hochuekkito [50]. In this study, it was found that hochuekkito effectively blocked the increase in bacterial loads in the sputum, accompanied by radiological and nutritional improvements, during 24-week treatment in combination with anti-MAC antimicrobial chemotherapy [50].…”
Section: In Vivo Efficacy Of Herbal Medicines As Immunoadjunctive mentioning
confidence: 90%
See 1 more Smart Citation
“…Hochuekkito (Bu Zhong Yi Qi Tang) (10 herbs including Daucus carota , Astragalus membranaceus , Atractylodes lancea , Bupleurum falcatum , and Angelica acutilob ), is occasionally used in Japan for the control of a weak constitution, physical weariness, anorexia, and gastrointestinal hypomotility. A recent randomized controlled trial enrolling 18 patients with an advanced stages of MAC disease revealed the significant therapeutic efficacy of hochuekkito [50]. In this study, it was found that hochuekkito effectively blocked the increase in bacterial loads in the sputum, accompanied by radiological and nutritional improvements, during 24-week treatment in combination with anti-MAC antimicrobial chemotherapy [50].…”
Section: In Vivo Efficacy Of Herbal Medicines As Immunoadjunctive mentioning
confidence: 90%
“…A recent randomized controlled trial enrolling 18 patients with an advanced stages of MAC disease revealed the significant therapeutic efficacy of hochuekkito [50]. In this study, it was found that hochuekkito effectively blocked the increase in bacterial loads in the sputum, accompanied by radiological and nutritional improvements, during 24-week treatment in combination with anti-MAC antimicrobial chemotherapy [50].…”
Section: In Vivo Efficacy Of Herbal Medicines As Immunoadjunctive mentioning
confidence: 90%
“…They also showed that body weight increased from baseline to the end of the trial in the TJ-41 group, but remained unchanged in the control group. Compared to the control group, patients with Mycobacterium avium complex disease showed increased body weight and serum albumin levels when treated with TJ-41 ( 26 ). In the present study, body weight and %IBW in Group A were significantly increased after 3 months of treatment, but not in Group B.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudoaldosteronism by shakuyakukanzoto was observed during 2 weeks after the start of treatment , but no ADR to shakuyakukanzoto were observed in longer treatment periods such as 4 weeks or 16 weeks . In addition, no ADR were reported for hochuekkito containing 1.5 g/day licorice, given for 24 weeks . As a result, pseudoaldosteronism by licorice is considered to depend on more than only the treatment period.…”
Section: Discussionmentioning
confidence: 99%